Bacteria-free minicircle DNA system to generate integration-free CAR-T cells. Issue 1 (20th July 2018) - Cheng, Chen; Tang, Na; Li, Jiaxin; Cao, Shiwei; Zhang, Tongtong; Wei, Xiaofei; Wang, Haoyi
Abstract : Background: Chimeric antigen receptor T (CAR-T) cells engineered with lentiviral and retroviral vectors have been successfully applied to treat patients with B cell malignancy. However, viral integration in T cells has the potential risk of mutagenesis, and viral vector production demands effort and is costly. Using non-integrative episomal vector such as minicircle vector to generate integration-free CAR-T cells is an attractive option. Methods and results: We established a novel method to generate minicircle vector within a few hours using simple molecular biology techniques. Since no bacteria is involved, we named these vectors bacteria-free (BF) minicircle. In comparison with plasmids, BF minicircle vector enabled higher transgene expression and improved cell viability in human cell line, stem cells and primary T cells. Using BF minicircle vector, we generated integration-free CAR-T cells, which eliminated cancer cells efficiently both in vitro and in vivo. Conclusion: BF minicircle vector will be useful in basic research as well as in clinical applications such as CAR-T and gene therapy. Although the transgene expression of minicircle vector lasts apparently shorter than that of insertional lentivirus, multiple rounds of BF minicircle CAR-T cell infusion could eliminate cancer cells efficiently. On the other hand, a relatively shorter CAR-T cell persistence provides an opportunity to avoid serious side effects such as cytokine storm or on-target off-tumour toxicity.